2011
DOI: 10.1289/ehp.1002739
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and Apnea and Bradycardia in High-Risk Infants on Home Monitors

Abstract: Background: Evidence suggests that increased ambient air pollution concentrations are associated with health effects, although relatively few studies have specifically examined infants.Objective: We examined associations of daily ambient air pollution concentrations with central apnea (prolonged pauses in breathing) and bradycardia (low heart rate) events among infants prescribed home cardiorespiratory monitors.Methods: The home monitors record the electrocardiogram, heart rate, and respiratory effort for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
2
14
0
1
Order By: Relevance
“…Panel and other epidemiological studies have shown associations between ozone levels and increases in blood pressure and heart rate (Cakmak et al, 2011), changes in the T wave of the ECG (Bhaskaran et al, 2011), increases in ischemic cardiovascular events (Bogdanov and Osterud), bradycardia in high risk infants (Peel et al, 2011), and ventricular tachycardia (Bartell et al, 2013). However, in panel and epidemiology studies where multiple ambient pollutants are involved, it is difficult to disentangle the effects of ozone from other pollutants including PM.…”
Section: Discussionmentioning
confidence: 99%
“…Panel and other epidemiological studies have shown associations between ozone levels and increases in blood pressure and heart rate (Cakmak et al, 2011), changes in the T wave of the ECG (Bhaskaran et al, 2011), increases in ischemic cardiovascular events (Bogdanov and Osterud), bradycardia in high risk infants (Peel et al, 2011), and ventricular tachycardia (Bartell et al, 2013). However, in panel and epidemiology studies where multiple ambient pollutants are involved, it is difficult to disentangle the effects of ozone from other pollutants including PM.…”
Section: Discussionmentioning
confidence: 99%
“…These short-term average lags for gases seem to be most relevant for other health outcomes. [22][23][24] To investigate confounding by air pollutants, we conducted bivariate analyses using a subset of the data where we had both the relevant data for each pollutant as well as apparent temperature. We evaluated potential effect modification by the same pollutants by adding an interaction term with apparent temperature and each pollutant in separate models.…”
Section: Discussionmentioning
confidence: 99%
“…For all pollutants examined, an average of the same day and previous 2 days were used (lag02). These short‐term average lags for gases seem to be most relevant for other health outcomes . To investigate confounding by air pollutants, we conducted bivariate analyses using a subset of the data where we had both the relevant data for each pollutant as well as apparent temperature.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in the maximum ozone level predicted increases in bradycardia and apnea in high-risk infants on home monitors. 12 Controlled human exposure to 1-hour exposures of diesel exhaust did not influence heart rhythm or variability in a UK study. 13 Increased spatial dispersion of myocardial repolarization, but not T-wave alternans, was seen after controlled human exposures to concentrated ambient particles, ozone, or a combination of the 2 exposures.…”
Section: Update 2010 To 2012: Cardiac Arrhythmia Arrhythmia Precursmentioning
confidence: 93%